Pulse wave velocity is an independent predictor of the longitudinal increase in systolic blood pressure and of incident hypertension in the Baltimore Longitudinal Study of Aging - Najjar, Samer S; Scuteri, Angelo; Shetty, Veena; Wright, Jeanette G; Muller, Denis C; Fleg, Jerome L; Spurgeon, Harold P; Ferrucci, Luigi; Lakatta, Edward G (Journal of the American College of Cardiology, 2008)
This study sought to evaluate whether pulse wave velocity (PWV), a noninvasive index of arterial stiffness, is a predictor of the longitudinal changes in systolic blood pressure (SBP) and of incident hypertension. Although arterial stiffness is believed to underlie, in part, the age-associated changes in SBP, particularly at older ages, few longitudinal studies in humans have examined the relationship between arterial stiffness and blood pressure. Pulse wave velocity was measured at baseline in 449 normotensive or untreated hypertensive volunteers (age 53 +/- 17 years). Repeated measurements of blood pressure were performed during an average follow-up of 4.9 +/- 2.5 years. After adjusting for covariates including age, body mass index, and mean arterial pressure, linear mixed effects regression models showed that PWV was an independent determinant of the longitudinal increase in SBP (p = 0.003 for the interaction term with time). In a subset of 306 subjects who were normotensive at baseline, hypertension developed in 105 (34%) during a median follow-up of 4.3 years (range 2 to 12 years). By stepwise Cox proportional hazards models, PWV was an independent predictor of incident hypertension (hazard ratio 1.10 per 1 m/s increase in PWV, 95% confidence interval 1.00 to 1.30, p = 0.03) in individuals with a follow-up duration greater than the median. Pulse wave velocity is an independent predictor of the longitudinal increase in SBP and of incident hypertension. This suggests that PWV could help identify normotensive individuals who should be targeted for the implementation of interventions aimed at preventing or delaying the progression of subclinical arterial stiffening and the onset of hypertension.